NURSES KNOWLEDGE WITH ACCEPTANCE WEIGH IMPLEMENTATION (Studies in Dr. Sayidiman Hospital Magetan) - Viera Agustin; Arif Wijaya; Yunan Yusuf Habibi (Jurnal Keperawatan, 2014)
Along with the development of society, in the health sector there was an increase in demand for services both in quantity and quality. To improve the performance of nurses in the field of nursing management especially acceptance weigh implementation is unoptimal. This could happen due to a lack of knowledge of nurses about the implementation of the concept of weighing acceptance. The purpose of this study was to determine the relationship of nursing knowledge with the implementation of acceptance weighing studied in inpatient unit room of Dr. Sayidiman Hospital Magetan. Analytical Methods Cross-sectional study that researchers take measurements or research at a time. Population of 59 nurses with samples taken all inpatient room nurses as many as 59 people. The technique used in this study was the total sampling technique. Data collection was using questionnaires. Independent variables of knowledge nurses about the concept of acceptance weigh and dependent variable of acceptance weigh implementation. Data processing was done with the editing, coding, scoring, tabulating and using the Pearson correlation test. The results of the 59 respondents were knowledge about the concept of acceptance weighing that the nurses approaching the maximum value with known average value of 11.69, while for implementation thank weigh with known average value of 9.24 with had a correlation coefficient with the implementation of acceptance weigh was the significance value p-value = 0.000> 0.05 where the value of r = 0.597. By using the Pearson test with SPSS 16 of the two variables was found that p count is smaller than the table is 0.000 p <0.05 means that H1 is accepted, H0 is rejected. The conclusion of this study, which means there was a connection between nurses’ knowledge and acceptance weigh implementation.Keywords: nurses knowledge, implementation acceptance weigh